The Position of the Deed of Sale and Purchase Made by the Land Deed Official for Children Under the Guardianship Based on Court Determination - Ridwan, Muhammad Hidayat; Bawono, Bambang Tri (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2023)
The aim of this research is to find out and analyze the position of the PPAT deed for children who are not yet legally competent, who are authorized to the guardian based on a court decision and the legal consequences of the position of the PPAT deed for children who are not yet legally competent, who are authorized to the guardian based on a court decision. The research method used is normative juridical, namely an approach that uses a positivist legislative concept which states that law is identical to written norms, so this research is closely related to libraries because it will require secondary data in libraries. Based on the results of the research and discussion, it was concluded that. The Position of the Sale and Purchase Deed Made by the Land Deed Official (PPAT) for Children Under the Guardian's Care Based on Court Determination. The PPAT Deed serves as a means of proof in the form of an authentic deed, in order to provide guarantees, protection and fair legal certainty as well as equal treatment before the law, regarding certain circumstances, events or legal acts. This is in line with the progressive legal theory put forward by Sajipto Raharjo. Legal consequences of a Sale and Purchase Deed made by a Land Deed Official (PPAT) on children under the guardianship of a guardian based on a court decision. By making an authentic deed as evidence in the legal action, then the parties can be more aware of the consequences of their actions so that the interests concerned receive reasonable legal protection. Legal actions that result in the transfer of rights from one legal subject to another legal subject, thereby causing the loss of authority over the land. In this way, PPAT is in line with the theory of the workings of law put forward by William Chamblliss and Robert B Saidman. Keywords: Competent; Court; Land.